Influence Factors on Income Smoothing in Manufacturing Companies: Evidence from Indonesia's Stock Exchange: Faktor-Faktor yang Mempengaruhi Perataan Laba (Income Smoothing) pada Perusahaan Manufaktur: Bukti dari Bursa Efek Indonesia - Eny Maryanti; Biduri , Sarwenda; Kumala Sari , Herlinda Maya; Fauziah, Luluk Putri (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the determinants of income smoothing in Indonesian manufacturing firms listed on the stock exchange during 2016-2021. The research examines the impact of Institutional Ownership, Managerial Ownership, Return on Assets, Debt to Equity Ratio, and Ln Total Sales on Income Smoothing using binary logistic regression analysis. The findings reveal that Institutional Ownership, Managerial Ownership, and firm size significantly influence income smoothing, while Financial Leverage and Profitability do not exhibit significant effects on Income Smoothing. These results contribute to the understanding of income smoothing practices and hold implications for corporate governance and financial reporting practices in emerging markets. Highlight: Determinants of Income Smoothing: This study delves into the factors driving income smoothing in Indonesian manufacturing companies listed on the stock exchange between 2016 and 2021. Influential Factors: Institutional Ownership, Managerial Ownership, and firm size are identified as significant influencers of income smoothing, shedding light on their impact within this context. Implications for Governance and Reporting: The study's outcomes offer valuable insights for corporate governance practices and financial reporting strategies, particularly in the dynamic landscape of emerging markets. Keyword: Income Smoothing, Manufacturing Firms, Institutional Ownership, Managerial Ownership, Emerging Markets